The Night Before Christmas - Vasilatos, Jerry A.; Elfman, Danny, 1953- (USA Loew's, 1941)
Two items were invented to facilitate the filming of the movie: One was a "light alarm" which would warn the animators if any of the stage lights failed to come on. The other was a system that enabled a puppeteer to seamlessly switch to a replacement puppet if a puppet broke during a shot. Prior to this, either situation, a light failing to come on or a puppet breaking would destroy a shot.
Well, a mouse *is* stirring... And he's having fun playing with the toys, until he mistakes Tom for a stuffed toy and wakes him up.
Languages : English, Turkish Subtitles : No Subtitles
Keywords: Animation; Comedy; Short; Family